2012
DOI: 10.2174/187152412800792742
|View full text |Cite
|
Sign up to set email alerts
|

Stability, Disposition, and Penetration of Catalytic Antioxidants Mn-Porphyrin and Mn-Salen and of Methylprednisolone in Spinal Cord Injury

Abstract: This study measured the time courses of concentration changes following administration of the catalytic antioxidants Mn (III) tetrakis (4-benzoic acid) porphyrin (MnTBAP) and Mn (III) 3-methoxy N, N' bis (salicyclidene) ethylenediamine chloride (EUK-134) in blood and cerebrospinal fluid (CSF) of rats with a spinal cord injury (SCI) and sham controls. Parallel measurements were made for methylprednisolone, the only drug presently used clinically for treating SCI. The time courses kinetically characterized the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…We also demonstrated that the MP’s blood–spinal cord barrier penetrating ratio was much higher than MnTBAP (20% versus 4%) [50]. However, our results of behavioral tests demonstrated that with lower ability of penetrating the blood–spinal cord barrier, MnTBAP reached appropriate targets and more effectively improved the functional recovery than the standard treatment of SCI by MP, further supporting the candidacy of MnTBAP in treating SCI.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…We also demonstrated that the MP’s blood–spinal cord barrier penetrating ratio was much higher than MnTBAP (20% versus 4%) [50]. However, our results of behavioral tests demonstrated that with lower ability of penetrating the blood–spinal cord barrier, MnTBAP reached appropriate targets and more effectively improved the functional recovery than the standard treatment of SCI by MP, further supporting the candidacy of MnTBAP in treating SCI.…”
Section: Discussionmentioning
confidence: 60%
“…The standard regimen of MPSS, given intravenously (iv), consists of 30 mg/kg as a bolus dose followed by 5.4 mg/kg/h as a maintenance dose. The maximum MP concentration ratio of cerebrospinal fluid to blood is nearly 20% following iv administration [50]. According to this ratio, a 6 mg/kg bolus dose and a 1.08 mg/kg/h maintenance dose of MPSS given intrathecally equals the standard clinical regimen of MPSS given iv.…”
Section: Methodsmentioning
confidence: 99%
“…The ability to scavenge ROS may be exerted through its urethane groups [28,29]. Possibly ESHU’s antioxidant effects may be increased with higher concentrations [46]. Our observations point at antioxidation as a potential mechanism of ESHU-promoted BMSC transplant survival.…”
Section: Discussionmentioning
confidence: 81%
“…We compared the penetrating ability of MnTBAP to methylprednisolone (MP), the only drug used clinically to treat SCI. We found that, despite the much lower penetration of the blood-spinal cord barrier (BSB) by MnTBAP compared with MP, its higher stability allows a lower dose of MnTBAP to produce a higher concentration in the CSF than does higher doses of MP [ 42 ]. Moreover, we demonstrated that MnTBAP (10 mg/kg) given intraperitoneally (i.p.)…”
Section: Introductionmentioning
confidence: 99%